Dynamic Models for Seaweed Cultivation Development in The Waters of Luwu and Palopo Regency, South Sulawesi - Waluyo Waluyo; Yonvitner Yonvitner; Etty Riani; Taslim Arifin (Diponegoro University, 2020)
Waters carrying capacity in the seaweed of Eucheuma cottonii cultures should be a concern for optimum seaweed culture. Carrying capacity can determine by Ecological Footprint (EF) analysis, which in this research use footprint production, and mas balance nitrate analysis. This research on Mei 2015 (1st transitional season) and September 2015 (2nd transitional season) in Luwu and Palopo, South Sulawesi. Map and land use analyzed with geographic information systems (GIS). The results showed that the Ecological Footprint Production (EFP) in Luwu waters is 67,88 ton/capita/year, or equivalent to 235,823.93 tons/year. Based on the analysis of the availability of water for seaweed is 38,374.69 hectares, it can produce seaweed (biocapacity) for 922,928.96 tons/year and the number of farmers that allows for use the waters is 13,595 capita. The Ecological Footprint Production (EFP) in Palopo waters is 3.08 ton/capita/year, or equivalent to 4,589.99 tons/year. Water availability analysis is 979.82 hectares can produce seaweed (biocapacity) for 10,115.34 ton/year and the number of farmers that allows for use the waters is 3,276 capita. Based on the four scenario simulation management results of the development seaweed cultivation Eucheuma cottonii in Luwu and Palopo Regency is based on the present waste input, pressing inputs of waste into the waters of 10%, 25% and 50% yield different waters biocapacity. The results comparison between biocapacity and Ecological Footprint, ecological status for Luwu and Palopo waters are still in sustainable use. Based on those simulation results showed that in the second scenario by pressing the waste input by 10% from the existing waste input, as well as assuming the availability of water utilizing the entire area of 38,374.69 hectares continuously (on the years scale of 2008-2030), it will produce the highest biocapacity waters in the amount of 8,257,274.94 tons/year. So with the management of seaweed in Palopo with the second scenario, assuming the availability of water utilizing the entire area of 979.82 hectares will produce the highest waters biocapacity of 14,306.92 tons/year.